Implementing annotation strategies in reading scholar articles prototype - Zaihosnita Hood (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study explores the issue of annotation strategies and types used by researchers when reading scholarly articles during research activities. Researchers are active readers who make annotations when reading scholarly articles. Annotation types, such as highlight, underline, comment, and writing keywords, are often found in researchers’ annotated articles. Previous studies have shown that researchers forgot their intention after annotation, and their annotations were incomplete, resulting in a loss of value. We begin by designing early annotation strategies and types based on a literature review. We conducted an observation and interview session to verify the proposed annotation strategies and types, including collecting feedback from the researchers. A prototype was built and tested by 38 researchers during an evaluation session. The results showed that researchers have their annotation strategies and types when reading scholarly articles. They accepted the proposed annotation strategies and types and found them useful, meaningful, and usable.